Analisis Tingkat Kepuasan Mahasiswa Terhadap Pelayanan Laboratorium Teknik Industri Universitas Muhammadiyah A.R. Fachruddin - Jihan Kamilia Hanifah; Rahmat Saputra (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
The research results showed that the cleanliness aspect of the laboratory room received the highest level of satisfaction with 15.4% of respondents very satisfied and 48.7% satisfied. However, there was dissatisfaction with the lighting aspect with 2.6% of respondents dissatisfied and 4.9% very dissatisfied. The appearance and neatness of laboratory staff received the highest rating of very satisfied at 20.5%, while the response or speed of service and ease of communication access received several ratings of very dissatisfaction. In the aspect of equipment and materials, ease of use and the ability of tools and materials to help with work obtained the highest level of satisfaction with 12.8% of respondents being very satisfied. Overall, the user satisfaction level of the UNIMAR Industrial Engineering laboratory is quite satisfactory. The results of this research can provide input for laboratory managers to improve service quality, especially in the aspects of lighting and completeness of tools and materials, as well as speed and ease of access to communication with laboratory staff. It is hoped that these findings can support continuous improvement efforts in laboratory services to improve student learning experiences and academic achievements in the Industrial Engineering study program.Keywords: Student Satisfaction, Laboratory Services, SERVQUAL, Industrial Engineering